Mass social contact interventions and their effect on mental health related stigma and intended discrimination - Evans-Lacko Sara; London Jillian; Japhet Sarah; Rüsch Nicolas; Flach Clare; Corker Elizabeth; Henderson Claire; Thornicroft Graham (BMC, 2012)
Abstract Background Stigma and discrimination associated with mental health problems is an important public health issue, and interventions aimed at reducing exposure to stigma and discrimination can improve the lives of people with mental health problems. Social contact has long been considered to be one of the most effective strategies for improving inter-group relations. For this study, we assess the impact of a population level social contact intervention among people with and without mental health problems. Methods This study investigated the impact of social contact and whether presence of specific facilitating factors (equal status, common goals, cooperation and friendship potential): (1) improves intended stigmatising behaviour; (2) increases future willingness to disclose a mental health problem; and (3) promotes behaviours associated with anti-stigma campaign engagement. Two mass participation social contact programmes within England's Time to Change campaign were evaluated via a 2-part questionnaire. 403 participants completed initial questionnaires (70% paper, 30% online) and 83 completed follow-up questionnaires online 4-6 weeks later. Results This study investigated the impact of social contact and whether presence of specific facilitating factors (equal status, common goals, cooperation and friendship potential): (1) improves intended stigmatising behaviour; (2) increases future willingness to disclose a mental health problem; and (3) promotes behaviours associated with anti-stigma campaign engagement. Two mass participation social contact programmes within England's Time to Change campaign were evaluated via a 2-part questionnaire. 403 participants completed initial questionnaires (70% paper, 30% online) and 83 completed follow-up questionnaires online 4-6 weeks later. Campaign events facilitated meaningful intergroup social contact between individuals with and without mental health problems. Presence of facilitating conditions predicted improved stigma-related behavioural intentions and subsequent campaign engagement 4-6 weeks following social contact. Contact, however, was not predictive of future willingness to disclose mental health problems. Conclusions Findings emphasise the importance of facilitating conditions to promote positive social contact between individuals and also suggest that social contact interventions can work on a mass level. Future research should investigate this type of large scale intervention among broader and more representative populations.